Challenges in evaluating impact of sanctions – political vs economic perspective - Stępień, Beata; Pospieszna, Paulina; Skrzypczyńska, Joanna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
The aim of this paper is twofold: to highlight the need of combining economic and political perspectives in analyzing sanctions outcomes, and to list and elaborate on challenges connected with uniting these two standpoints and creating cohesive and valid measurement methods. We not only credit this fusion as useful, but necessary to evaluate sanctions’ efficiency and effectiveness. We display these challenges in sanctions’ assessment and measurement by systematizing what we already know about the sanction effectiveness in political science and economics literature and by demonstrating strengths and weaknesses of some already published effectiveness evaluations. The paper is the part of the larger research project that we recently embarked upon with aim to analyze the onset, economic impact and effectiveness of sanctions imposed by the European Union

Cel tego artykułu jest dwojaki. Pierwszy, to podkreślenie konieczności połączenia perspektywy ekonomicznej i politycznej w ocenie skutków sankcji. Drugi, to diagnoza i analiza wyzwań związanych z połączeniem tych perspektyw w taki sposób, aby stworzyć spójny oraz rzetelny merytorycznie i metodycznie sposób pomiaru tego zjawiska. Połączenie perspektywy ekonomicznej i politologicznej uznajemy nie tyle za pożyteczne, co niezbędne do prawidłowej oceny efektywności i skuteczności sankcji. Wyzwania związane z integrowaniem perspektyw i wypracowaniem narzędzi pomiaru prezentujemy przez pryzmat krytycznej analizy dotychczasowych badań dotyczących oceny skuteczności i efektywności sankcji, ukazując każdorazowo mocne i słabe strony zastosowanego podejścia. Artykuł jest częścią większego projektu dotyczącego przesłanek, ekonomicznego wpływu i skuteczności sankcji nakładanych przez Unię Europejską.
Wyzwania w ocenie wpływu sankcji – perspektywa polityczna a ekonomiczna
Keywords: international sanctions; effectiveness of economic sanctions; politics of sanctions; effectiveness; efficiency; sankcje międzynarodowe; skuteczność sankcji gospodarczych; polityka sankcji; skuteczność; efektywność